2020
DOI: 10.1001/jamanetworkopen.2020.1929
|View full text |Cite
|
Sign up to set email alerts
|

Rates of Overall Survival and Intracranial Control in the Magnetic Resonance Imaging Era for Patients With Limited-Stage Small Cell Lung Cancer With and Without Prophylactic Cranial Irradiation

Abstract: IMPORTANCE Historical data suggest that there is an overall survival benefit associated with prophylactic cranial irradiation (PCI) in patients with small cell lung cancer (SCLC). However, as the fidelity of magnetic resonance imaging (MRI) of the brain continues to improve, this idea is now being questioned, with recent research showing no survival benefit associated with PCI in extensive-stage SCLC; however, the role for PCI is not clear in patients with limited-stage SCLC (LS-SCLC).OBJECTIVE To report the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 18 publications
1
47
0
2
Order By: Relevance
“…Although brain metastases are improbable in early stage NSCLC without central neurologic symptoms [ 13 ], the risk of brain metastasis, especially in SCLC is omnipresent [ 14 ]. Large studies show bad survival rates for patients with limited [ 15 ] and extended disease [ 16 – 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although brain metastases are improbable in early stage NSCLC without central neurologic symptoms [ 13 ], the risk of brain metastasis, especially in SCLC is omnipresent [ 14 ]. Large studies show bad survival rates for patients with limited [ 15 ] and extended disease [ 16 – 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Aktuelle, prospektive Studiendaten, die auch die konsequent ein MRT als Entscheidungskriterien verwenden, liegen nicht vor. Retrospektive Analysen aus einzelnen Zentren deuten einen begrenzten klinischen Nutzen für eine prophylaktische Ganzhirnbestrahlung bei negativem Schädel-MRT an [8]. Nach der aktuellen Leitlinie sollte dennoch allen Patienten mit Remission nach Abschluss der Radiochemotherapie, die sich in gutem sonstigem Gesundheitszustand befinden und bei denen in einer aktuellen MRT des Schädels eine Hirnmetastasierung ausgeschlossen wurde, eine prophylaktische Schädelbestrahlung angeboten werden.…”
Section: Prophylaktische Ganzhirnbestrahlung Im Stadium IIIunclassified
“…Among these inconclusive studies, most studies did not perform routine brain-MRI at baseline to exclude BM. In fact, in the LS-SCLC studies that did report baseline MRI in (all or some) patients, 4 out of 6 studies found no significant improvement in BM incidence after PCI [18] , [25] , [26] , [27] and 3 out of 4 studies observed no OS benefit [27] , [28] , [29] .…”
Section: Discussionmentioning
confidence: 99%